SOCIO-DEMOGRAPHIC DETERMINANTS OF MENTAL DISORDERS - Zeb, Junaid; Shah, Muhammad Tariq; Zaman, Haidar; Farooq, Muhammad Umer; Moosa, Muhammad; Khattak, Muhammad Saleem; Ambareen, Saba; Habib, Sadaf (Pakistan Journal of Physiology, 2016)
Background: Having a sound mind in a sound body is vital to make a stable society. Even more vital is to find, diagnose, and treat mental disorders before they lead society to suffer. About 10 to 17% of general population in Pakistan suffers from mental disorders and it spends only 0.4% of the meagre health budget on mental health. This study aimed to describe the socio-demographic factors of mental illnesses in local population. Methods: This was a cross-sectional descriptive study conducted in Ayub Teaching Hospital, Abbottabad in 6 months from March to August 2016. Data were collected from 104 patients who were selected randomly by convenient non-probability technique and analysed using SPSS-23. Results: Out of total 104 patients, 56 were males and 48 were females; 40.83% were from urban while 59.62% were from rural areas. Singles were 43.3%, married were 48.1%, while 4.8% were divorced and 3.8% were widowed. Regarding socioeconomic status, 90.4% patients were of low socioeconomic class, 7.7% were of middle, while 21.9% were of high socioeconomic class. All patients were Muslims, 59.6% were living in joint family, 28.8% in nuclear family, 9.6% in extended, 0.9% in commune, and 0.9% in non-family system. Twenty-seven (26%) patients gave a positive family history of mental disorders. Behaviour of community with 85.6% patients was caring, 8.7% patients were kept in isolation, while 5.8% patients said that they had been neglected by the community. Depression (45.2%) followed by anxiety (11.5%), dissociative disorder (5.8%), and schizophrenia (5.8%) were the main findings. Conclusion: Mental disorders were more prevalent in females, young age, married people, living in urban areas with poor hygienic measure, low socioeconomic class and those with significant family history. Pak J Physiol 2016;12(4):33-6